Parenting Styles, Sexual Abuse and Self-esteem as Predictors of Sexual Orientation among Undergraduates - Ajayi, Ifeoluwa O.; Olapegba, Peter O.; Uye, Emmanuel E (Universitas Negeri Surabaya, 2025)
Background: Sexual orientation has become an emerging issue that affects different populations and cultures in Africa including Nigeria. Studies done on predictors of sexual orientation come with varied results.Objective: This study investigates parenting styles, sexual abuse and self-esteem as likely predictors of sexual orientation among undergraduates in tertiary institutions in Ibadan, Nigeria. Method: Cross-sectional method was adopted while purposive sampling technique was used to select the study population. Data were collected from 472 undergraduates using validated questionnaires and analysed using multiple regressions and independent sample t-test. Two hypotheses were tested and accepted at p =.001 level of significance. Results: The result revealed that parenting styles, sexual abuse and self-esteem jointly predicted sexual orientation among study participants. Moreover, parenting styles, sexual abuse and self-esteem independently predicted sexual orientation among study participants. Conclusion: Parenting styles, sexual abuse and self-esteem are excellent predictors of sexual orientation among study participants. The novelty of this finding is that sexual orientation is less openly discussed among study population. Keywords: Parenting styles; self-esteem; sexual abuse; sexual orientation; undergraduates Abstrak Latar belakang: Orientasi seksual telah menjadi masalah yang muncul yang mempengaruhi populasi dan budaya yang berbeda di Afrika termasuk Nigeria. Studi yang dilakukan pada prediktor orientasi seksual memiliki hasil yang bervariasi. Tujuan: Penelitian ini menyelidiki gaya pengasuhan, pelecehan seksual dan harga diri sebagai prediktor yang mungkin untuk orientasi seksual di kalangan mahasiswa di perguruan tinggi di Ibadan, Nigeria. Metode: Metode cross-sectional diadopsi sementara teknik pengambilan sampel purposif digunakan untuk memilih populasi penelitian. Data dikumpulkan dari 472 mahasiswa dengan menggunakan kuesioner yang telah divalidasi dan dianalisis menggunakan regresi berganda dan uji-t sampel independen. Dua hipotesis diuji dan diterima pada tingkat signifikansi p = .001. Hasil: Hasil penelitian menunjukkan bahwa gaya pengasuhan, pelecehan seksual, dan harga diri secara bersama-sama memprediksi orientasi seksual di antara para peserta penelitian. Selain itu, gaya pengasuhan, pelecehan seksual dan harga diri secara independen memprediksi orientasi seksual di antara peserta penelitian. Simpulan: Gaya pengasuhan, pelecehan seksual, dan harga diri adalah prediktor yang sangat baik untuk orientasi seksual di antara para peserta penelitian. Hal baru dari temuan ini adalah bahwa orientasi seksual kurang didiskusikan secara terbuka di antara populasi penelitian. Kata Kunci: Gaya pengasuhan; harga diri; mahasiswa; pelecehan seksual; orientasi seksual.